Alpha-, beta-, gamma-radiometric measurements using semiconductor detectors - Grigoryev, A.N.; Sakun, A.V.; Marushchenko, V.V.; Bilyk, Z.V.; Litvinov, Yu.V.; Chernyavsky, O.Yu.; Voronkin, E. (Functional Materials, 2014)
Referring to shortcomings of modern radiation detection and monitoring devices, an operable prototype of the device for determination of the gamma radiation exposure dose rate within the range from 10 μ R/h to 1000 R/h, with the energy γ -radiation sensitivity range from 50 keV to 3 MeV, has been offered. The prototype is able to register the α-radiation and β-radiation flux density. The device operates using two detection units and a two-channel counting unit. Registration of the exposure dose rate is provided by using CdTe detector, and registration of the α-radiation and β-radiation flux density is provided by using Si detector.